(untitled) (Research, Society and Development, 2020)
Infiltration is the process of water entering the soil through its surface. The knowledge of this process is vital for establishing soil conservation guidelines and water, plan and design irrigation systems, indicating the amount of water available to plants, calculate groundwater recharge rates, runoff rates in precipitation events. To obtain data on infiltration, infiltrometers are generally used, which are used in field tests, with the concentric ring infiltrometer (IAC) being the most used to determine the basic water infiltration rate in the soil (VIB). This work aimed to obtain the infiltration data of an urban watershed to subsidize the input data and adjustments in runoff models in the Córrego Sem Nome basin in the municipality of Ilha Solteira - SP, tests were carried out at 6 points establishing their areas of relationships by means of Thiessen polygons, no spatial correlation was found between the points, the three parameters being studied: initial infiltration rates, final and constant decay infiltration rates, which corroborates the extensive literature on the subject which confirms that there is no spatial correlation of the infiltration properties over long distances, which further emphasizes the need to obtain real values ​​of water infiltration in the soil, in order to determine the values ​​of the input parameters for Horton’s equation.